Improved characterization of heterogeneous permeability in saline aquifers from transient pressure data during freshwater injection - Kang, Peter K.; Lee, Jonghyun; Fu, Xiaojing; Lee, Seunghak; Kitanidis, Peter K.; Juanes, Ruben (AMER GEOPHYSICAL UNION, 2017)
Managing recharge of freshwater into saline aquifers requires accurate estimation of the heterogeneous permeability field for maximizing injection and recovery efficiency. Here we present a methodology for subsurface characterization in saline aquifers that takes advantage of the density difference between the injected freshwater and the ambient saline groundwater. We combine high-resolution forward modeling of density-driven flow with an efficient Bayesian geostatistical inversion algorithm. In the presence of a density difference between the injected and ambient fluids due to differences in salinity, the pressure field is coupled to the spatial distribution of salinity. This coupling renders the pressure field transient: the time evolution of the salinity distribution controls the density distribution which then leads to a time-evolving pressure distribution. We exploit this coupling between pressure and salinity to obtain an improved characterization of the permeability field without multiple pumping tests or additional salinity measurements. We show that the inversion performance improves with an increase in the mixed convection ratiothe relative importance between viscous forces from injection and buoyancy forces from density difference. Our work shows that measuring transient pressure data at multiple sampling points during freshwater injection into saline aquifers can be an effective strategy for aquifer characterization, key to the successful management of aquifer recharge.
Keywords: DENSITY GROUNDWATER-FLOW; RECOVERY ASR; HYDRAULIC CONDUCTIVITY; MIXED CONVECTION; THEORETICAL-ANALYSIS; SOLUTE TRANSPORT; COASTAL AQUIFER; JOINT INVERSION; CLIMATE-CHANGE; POROUS-MEDIA